Queensland Literature: Is it Different? - Winter, Gary (LiNQ (Literature in North Queensland), 2016)
The question of a literary representation of a distinctive Queensland identity invites discussion in several areas: to what extent does Queensland have a distinctive identity, and what evidence may be gleaned from literary texts to support the notion that this identity exists; what does it mean to be a Queenslander in the wider Australian context? This article will discuss Thea Astley, Jessica Anderson and David Malouf.